2007
DOI: 10.1038/sj.eye.6702871
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of optic nerve head configuration in various types of optic neuropathy with Heidelberg Retina Tomograph

Abstract: Purpose To test whether Heidelberg Retina Tomograph (HRT) is applicable to assess the optic nerve head (ONH) configuration of the atrophic phase of non-glaucomatous optic neuropathy when a default set of the reference plane is used. Methods Ten eyes with non-arteritic anterior ischaemic optic neuropathy (NAION), 17 eyes with Leber's hereditary optic neuropathy (LHON), 40 eyes with compressive optic neuropathy (CON) owing to chiasmal tumour, and 241 eyes of control individuals were examined with HRT using the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
1
2

Year Published

2007
2007
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 32 publications
0
13
1
2
Order By: Relevance
“…57 Cslo has also been used to assess the optic nerve head in chronicphase naion, and has shown that affected eyes have significantly thinner mean rnFl thickness and smaller rnFl crosssectional area than control eyes. 32,60 interestingly, Cslo has revealed thinning in all sectors, not solely those corresponding to the seg mental atrophy found on examination. 58,59 these findings suggest that rnFl loss in naion could extend beyond the region corresponding to the visible atrophy.…”
Section: Key Pointsmentioning
confidence: 94%
See 1 more Smart Citation
“…57 Cslo has also been used to assess the optic nerve head in chronicphase naion, and has shown that affected eyes have significantly thinner mean rnFl thickness and smaller rnFl crosssectional area than control eyes. 32,60 interestingly, Cslo has revealed thinning in all sectors, not solely those corresponding to the seg mental atrophy found on examination. 58,59 these findings suggest that rnFl loss in naion could extend beyond the region corresponding to the visible atrophy.…”
Section: Key Pointsmentioning
confidence: 94%
“…21 Confocal scanning laser ophthalmoscopy (Cslo; Figure 1b), scanning laser polari metry (slP; Figure 1c) and optical coherence tomo graphy (oCt; Figure 1d) are being used increasingly in the assessment of optic neuropathies and neuro degenerative conditions that affect the rnFl and optic nerve. [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] Ischemic optic neuropathies ischemic optic neuropathies are subdivided into anterior (primarily affecting the optic nerve head) and posterior (affecting the intraorbital portion of the optic nerve) sub types. Posterior ischemic optic neuropathies are by far the rarer of the two subtypes, and are characterized by the…”
mentioning
confidence: 99%
“…NAION occurs in an optic nerve head already susceptible to ischemia [11]. Another possible mechanism is the "discat-risk" that refers to a small optic nerve with a small or absent physiologic cup [18]. The physiologic cup of the optic nerve corresponds to the size of the scleral canal (the opening in the sclera through which the optic nerve exits the eye) [14] while the disc refers to the optic nerve.…”
Section: What Is Naion?mentioning
confidence: 99%
“…(49) O laser confocal de varredura também já foi usado para avaliar o nervo óptico na fase crônica da NOIA-NA e mostrou afilamento significativo da CFNR comparado com normal. 50 Estes métodos usualmente mostram afilamento da CFNR não apenas no local onde existe atrofia óptica visível mas também A análise quantitativa do DO revela na fase crô-nica afilamento significativo da CFNR, que se desenvolve ao longo de meses até estabilizar 6 meses após o evento. Estudos com o LCV indicam que olhos afetados tem redução importante da CFNR quando comparada com normais.…”
Section: Neuropatias óPticas Isquêmicasunclassified
“…Estudos com o LCV indicam que olhos afetados tem redução importante da CFNR quando comparada com normais. 50 Estudos com a TCO também mostram perda da CFNR e evidenciam que após a NOIA existe perda da CFNR não apenas no setor acometido pela perda de campo visual indicando que a perda de fibras pode ir além do local de palidez do DO. (51) O afilamento da CFNR também pode ser bem demonstrado na fase crônica da doença através do GDx.…”
Section: Neuropatias óPticas Isquêmicasunclassified